DEVELOPING A MODEL OF GENDER POLICY IN THE EDUCATION SYSTEM OF KAZAKHSTAN: A FOCUS ON HEALTH-SAVING PEDAGOGICAL CONDITIONS - Aigerim, Kussaiynkyzy; Myrzabike, Zhumabayeva (Top Journal of Public Policy and Administration (TJPPA), 2023)
This article aims to develop a model of gender policy in the education system of Kazakhstan, focusing on health-saving pedagogical conditions to ensure respectful and equitable treatment of all groups of students. The study uses a diagnostic survey method to identify and examine individual personality traits of the psychological, functional, and social sphere of learners. The model developed is based on gender equality, individual needs, and functional development, depending on personal self-perception, in the framework of the compulsory study of basic theoretical general education subjects. It has a humanistic and social provision for the personal gender needs of learners and related study of general education knowledge in core academic disciplines. The article emphasizes the importance of nurturing a developed and cultural personality of a student in the education system, considering various gender aspects that play an important role in full and harmonious development while avoiding discrimination factors that could create conditions for the suppression and humiliation of students’ personality. This study contributes to the formation of the entire gender education strategy in Kazakhstan, which is of significant importance in life.